A Prospective Randomized Study of Local In?ltration of Two Di?erent Concentrations of Ropivacaine for Postoperative Analgesia in Inguinal Hernia Repair - Macha Niranjan Reddy; Payal Jain; Mukesh Kumar Prasad; Gurdeep Singh Jheetay; Razi Shahid (Academia Anesthesiologica International, 2021)
Background: Postoperative pain management by surgical site infiltration has an edge over other methods of analgesia as it is simple and      has lesser side effects. This study was designed to compare the analgesic effects provided by two  different concentrations 0.25% and 0.50%   of Ropivacaine, a new amino amide local anesthetic agent. Subjects and Methods: Ninety six patients in each group scheduled for elective inguinal herniorrhaphy were randomly allocated by chit and box method to Group A(0.50%) and Group B(0.25%), spinal anesthesia was given. The surgical site was infiltrated after the end of surgery with 20 ml of drugs; Ropivacaine 0.5% in group A, Ropivacaine 0.25% in group B. Postoperatively hemodynamics were recorded from every 0 h to until 12 h. Postoperatively, rest pain, pain on coughing, and pain on movements were assessed using visual analog scale (VAS) score immediately at the end of the surgery and 2 hourly up to 12 h. The time of the first request for rescue analgesia was noted. Results: VAS scores at rest(P<0.027*), during coughing(P<0.001) and movements (P< 0.04) were higher in group B 0.25% and the time of rescue analgesia was higher with group B 0.25% when compared with other group A (P<0.001). Conclusion: Ropivacaine as an anesthetic in inguinal hernia repair for surgical infiltration is safe and effective in pain reduction, with very few adverse reactions at the concentration of 0.5%.